MELAKUKAN AUTHENTIC ASSESSMENTS DALAM PEMBELAJARAN AGAMA ISLAM - Saeful Anam (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
This article discussed about how an educator doing an assessment which appropriated to learning com-ponents. Because few educators are able to assess in appro-priate with the norm of learning assessment. As known in learning, the assessments were done either formative or summative. Further, there are two kinds of assessment, test and non-test assessment. In which, each of those assess-ments were divided into several aspects. Therefore, there are many ways which educator could do especially on Islamic learning, in order to know learner’s mastery toward concepts and religious values taught by the educator, and to be conti-nued into the implementation in daily life. Remember that the norm referenced assessment, criterion referenced assess-ment, and principal assessment could not be forgotten in assessing. By knowing those aspects, the educator will be able to classify the alteration given by learners for their competences through deeply assessments.Key words: Assessment, Authentic, Religious Learning